Obstetric complications and delivery methods in Indonesia - Hadi Ashar; Sri Supadmi; Ina Kusrini; Arita Murwani; Ismil Khairi Lubis; Muhamad Arif Musoddaq; Mohamad Samsudin; Hastin Dyah Kusumawardani; Diah Yunitawati; Felly Philipus Senewe; Tuti Susilowati (Universitas Airlangga, 2023)
HIGHLIGHTS Nearly a quarter of pregnant women experience pregnancy complications during the delivery process Caesarean section delivery is dominant among other methods, and 8.4% of mothers do not have any complications but choosing cesarean section delivery. ABSTRACT Objective: This study aimed to determine the delivery methods, indications and any associations between delivery methods and obstetric complications in Indonesia in 2018. Materials and Methods: This study analyzed data from the Basic Health Research (Riskesdas) 2018. The population and sample were married eligible women of 10 – 54 years old who had children, as many as 78,737 mothers. The variable taken in this study was the problems/complications during pregnancy as the independent variable, and the methods of delivery as the dependent variable. Chi-square test was used for comparison purposes. Logistic regression was run to relationship between complications and delivery methods. Results: Delivery indications were complications during the delivery process (23.23%), premature rupture of membranes (5.07%), obstructed labor (3.37%), transverse fetus (3.09%), bleeding (2.36%), and other complications (3.98%). Methods of delivery were expected delivery (81.45%), cesarean section (17.64%), and with other procedures (0.90%). Conclusion: Complications of labor correlate significantly with the methods of cesarean section. The cesarean section still dominated among other delivery modes, and there are still many mothers who did not have complications or no medical indications but choosing cesarean section delivery.